EFFECT OF DIFFERENT DIETARY LYSINE REGIMENS ON THE GROWTH PERFORMANCE AND ECONOMIC EFFICIENCY OF JAPANESE QUAILS - Y. Abbas; A. W. Sahota; M. Akram; K. Javed; M. Younus; S. Mehmood; S. Ahmad; Ikerma; A. S. Jatoi (Journal of Animal and Plant Sciences, 2016)
The present study aimed to examine the growth performance and economic efficiency involving 1440 day-old Japanese quail (Coturnix japonica) chicks at Avian Research and Training (ART) Centre, University of Veterinary and Animal Sciences, Lahore, Pakistan. Three dietary lysine levels (1.3, 1.4-1.2 & 1.5-1.3-1.1 %) in 3 different phases were allocated to four different close-bred stocks (Imported, Local-1, Local-2 and Local-3) of Japanese quails to assess their comparative growth performance by replicating each treatment for three times. The experimental day-old quail chicks were randomly divided into 36 experimental units of 40 chicks each. Quails under 1st treatment were fed a diet with 1.3 percent lysine throughout the grow-out period of 28 days, while, those under 2nd treatment were allotted diet with 1.4 percent lysine up to14 days of age and then subsequently reduced to 1.2 percent lysine up to 28 days. The 3rd treatment was split into 03 different phases. The first phase was up to 9th, 2nd up to 19th and 3rd up to 28th day by allotting diet containing 1.5, 1.3 and 1.1 % lysine, respectively. Weekly data on growth performance were recorded and analyzed through ANOVA technique in CRD under factorial arrangement. The comparison of means was carried out using DMR test by the help of SAS 9.1. Maximum (P<0.05) feed intake, body weight gain and improved FCR were observed in three phase dietary lysine regimen leading to maximum profit margin. However, close bred stocks could not show any significant difference in growth parameters.
Keywords: lysine regimens; growth performance; economics; close bred stock; Japanese quails